Communication Between the Disability Care Pioneers and the Situbondo Government - Yusi Putri Lailatul Musyarofah; Nur Annafi Farni Syam Mella; Ade Bagus Permana Putra; Slow Ahmadi (Fakultas Dakwah UIN Kiai Haji Achmad Siddiq Jember, 2024)
This article discusses the communication between the Disability Care Pioneers and the Situbondo Regency Government. Since 2018, Situbondo Regency has declared itself an inclusive district, aiming to encompass various sectors, including employment. However, the Situbondo Regency Government has not yet comprehensively initiated efforts to realize inclusive employment. In response, the Disability Care Pioneers of Situbondo, a non-profit organization, took the initiative to promote inclusive employment in the region. This article analyzes and describes the communication process and various factors influencing the communication between the Disability Care Pioneers and the Situbondo Regency Government. Through a descriptive case study research method, based on the constructivist paradigm, it was found that the initial communication aimed to build emotional proximity. The familial approach between the Disability Care Pioneers and relevant stakeholders fostered empathy and credibility, further reinforcing the commitment to inclusive employment. The Disability Care Pioneers established bonds that facilitated collaboration and synergy, as well as built a strong support network, which eased the integration of individuals with disabilities into the labor market and encouraged broader societal involvement. Additionally, this family-based, empathy-driven approach enhanced the organization's credibility, ensuring that inclusive employment became a tangible reality with a positive impact on the Situbondo community.